2021
DOI: 10.1590/1980-0037.2021v23e55654
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between postural changes and physical and functional variables in schoolchildren aged 6-12 years

Abstract: The aim of this study was to evaluate the prevalence of postural changes and their relationship with BMI, pain, postures adopted in activities of the daily living (ADL), physical activity practice, gender and age (6 to 12 years). This study is characterized as cross-sectional, quantitative and descriptive. The convenience sample consisted of 840 schoolchildren. Regarding the sample characteristics, 477 (56.79%) were female aged 6-12 years (average=8.90±1.71years). Evaluations were carried out at the school pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
3
0
3
Order By: Relevance
“…Nine studies conducted regression analyses [ 22 , 42 , 43 , 45 , 46 , 51 53 , 58 ] and ten studies used correlational analyses [ 35 , 44 , 47 – 50 , 54 – 56 , 59 ]. PA was self-reported in all studies and posture was measured in various ways including Dual-energy X-ray Absorptiometry (DXA) [ 51 ], Adam’s test [ 53 , 56 , 58 ], questionnaire [ 44 , 55 ] and qualitative assessment [ 46 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies conducted regression analyses [ 22 , 42 , 43 , 45 , 46 , 51 53 , 58 ] and ten studies used correlational analyses [ 35 , 44 , 47 – 50 , 54 – 56 , 59 ]. PA was self-reported in all studies and posture was measured in various ways including Dual-energy X-ray Absorptiometry (DXA) [ 51 ], Adam’s test [ 53 , 56 , 58 ], questionnaire [ 44 , 55 ] and qualitative assessment [ 46 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To detect and assess scoliosis the studies used the Scoliometer [ 52 ], dual energy X-ray absorptiometry (DXA) [ 51 ], Adams Test [ 53 , 56 , 58 ], and the Bunnel inclinometer The lumbar lordosis was assessed using several tools including the flexible ruler [ 35 ], spinal mouse [ 59 ], radiography [ 45 ] and the Bubble inclinometer [ 54 ]. Nine studies reported postural deformities using the following measures: McCloskey/Kanis method [ 22 ], New York Posture Rating (NYPR) test [ 49 ], posture grid and plumb line [ 42 ], radiograph measurement [ 43 ], Hoeger posture assessment method [ 50 ], Instrumento de Avaliação Postural (IAP) [ 47 ], The Jaroš and Lomíček test [ 48 ] and a questionnaire method [ 54 , 55 ]. One study had assessed the possible association between PA and valgus knee by observation and qualitative assessment [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estos hallazgos contribuyen a la comprensión de cómo y por qué se desarrollan estas desviaciones, y a la implementación de programas de prevención y rehabilitación, dado que algunos de los factores asociados son modificables. Bertoncello et al, (2021) São Paulo, Brasil 840 escolares 477 niñas de 6 a 12 años 363 niños de 6 a 12 años Evaluar la prevalencia de cambios posturales y su relación con IMC, dolor y posturas adoptadas en actividades de la vida diaria (AVD).…”
Section: Calidad Del Estudiounclassified
“…Sin embargo, existen trastornos en ciertas partes del cuerpo de manera específica, al momento de adoptar posiciones de manera incorrecta, estas pueden causar inestabilidad y desequilibrio (Kinga et al, 2021). De acuerdo con este último punto, debido a una perjudicial alineación postural, se acentúan aún más estas conductas de riesgo, ya que se normaliza adoptar una mala posición que conlleva a una mala higiene postural, además un bajo nivel de actividad física de manera regular, sobrepeso y obesidad, entre otros factores de riesgo (Bertoncello et al, 2021). Dado esto, su cuidado adecuado previene dolores de espalda, dolores de cuello, así también enfermedades como la cifosis, escoliosis, hernias, hiperlordosis, entre otras (Mejía-Balcázar, Aguilar-Aguilar & Mejía-Baraja, 2018), y el contexto escolar no es la excepción (Espinoza, 2018).…”
Section: Introductionunclassified